NEW BASELINE GLOMERULAR FILTRATION RATE ESTIMATION AS A GUIDANCE FOR NEPHRECTOMY STRATEGY IN LOCALIZED RENAL CELL CARCINOMA - Salman Aziz, Muhamad Abi; Mas`udi, Achmad Fayyad; Rahaju, Anny Setijo; Dewanti, Linda (Indonesian Urological Association, 2023)
Objective: This literature review aims to explain the role of nephrectomy in the treatment of localized RCC and its effects on postoperative renal function, as well as the role of the new baseline glomerular filtration rate (NBGFR) estimation method in the determination of the RCC method. Material & Methods: Articles were obtained through online searches using Pubmed, ScienceDirect, Web of Science, and Wiley Online Library using keywords NBGFR, renal function, nephrectomy, or localized renal cell carcinoma. Results: The development of several diagnostic factors as well as operative factors has made partial nephrectomy (PN) replace radical nephrectomy (RN) which for decades has been the main therapy in localized RCC. Postoperative determination of renal function is a crucial factor in the selection of therapies and several methods of determining NBGFR have been proposed in several previous studies. Conclusion: The NBGFR measurement method can be an accurate guide in the determination of nephrectomy methods in the treatment of localized RCC while use of computer software can help improve accuracy in the implementation of radical nephrectomy in RCC.